2011
DOI: 10.3390/cancers3011329
|View full text |Cite
|
Sign up to set email alerts
|

The Proteasome Inhibitor Bortezomib Sensitizes AML with Myelomonocytic Differentiation to TRAIL Mediated Apoptosis

Abstract: Acute myeloid leukemia (AML) is an aggressive stem cell malignancy that is difficult to treat. There are limitations to the current treatment regimes especially after disease relapse, and therefore new therapeutic agents are urgently required which can overcome drug resistance whilst avoiding unnecessary toxicity. Among newer targeted agents, both tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) and proteasome inhibitors show particular promise. In this report we show that a combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 53 publications
1
18
0
1
Order By: Relevance
“…According to the past studies, the most important mechanism of QUR-mediated sensitization is correlated with the regulating of numerous genes involved in the apoptosis and cell cycle (Chen, Wang, Zhuang, Zhang, & Lin, 2007;Jung, Heo, Lee, Kwon, & Kim, 2010;Youn, Jeong, Jeong, Kim, & Um, 2013). According to the results shown in Figure 3, as well as the Dijk et al (2011) study, KG-1 cells display a high-level resistance to rhTRAIL showing a cell viability of >85% at the rhTRAIL alone treatment. We found that the mechanism by which QUR leads to overcoming the cell resistance against TRAIL is probably due to the induction of DRs expression and the downregulation of p65, XIAP, c-IAP1, and c-IAP2.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…According to the past studies, the most important mechanism of QUR-mediated sensitization is correlated with the regulating of numerous genes involved in the apoptosis and cell cycle (Chen, Wang, Zhuang, Zhang, & Lin, 2007;Jung, Heo, Lee, Kwon, & Kim, 2010;Youn, Jeong, Jeong, Kim, & Um, 2013). According to the results shown in Figure 3, as well as the Dijk et al (2011) study, KG-1 cells display a high-level resistance to rhTRAIL showing a cell viability of >85% at the rhTRAIL alone treatment. We found that the mechanism by which QUR leads to overcoming the cell resistance against TRAIL is probably due to the induction of DRs expression and the downregulation of p65, XIAP, c-IAP1, and c-IAP2.…”
Section: Discussionmentioning
confidence: 75%
“…This finding is consistent with the results of the previous studies exploring the effect of QUR on the expression of the c-FLIP gene. For example, Manouchehri, Turner, and Kalafatis (2018) showed that QUR had no increasing or decreasing effect on the level of c-FLIP mRNA, but it was able to reduce the protein level of the c-FLIP gene.More comprehensive data about the c-FLIP expression at the protein level alongside with its possible role on the TRAIL signaling pathways may help us to establish more accurate information about the function of QUR in KG-1 cells Dijk et al (2011). studied the effect of bortezomib as a proteasome inhibitor in sensitizing KG-1 cells against TIA.…”
mentioning
confidence: 99%
“…Other report demonstrated that co‐treatment of TRAIL‐resistant meningioma cells with TRAIL and bortezomib made these cells susceptible to TRAIL by c‐FLIP down‐regulation (Koschny et al, ). Additionally, resistance of kasumi and ML‐2 acute myeloid leukemia (AML) cells to TRAIL attenuated via c‐FLIP and XIAP down‐regulation following their co‐treatment with TRAIL and bortezomib (Dijk et al, ). According to clinical studies, 18 cases of 30 patients with TRAIL‐resistant AML cancers were obviously sensitive to the pro‐apoptotic functions of bortezomib, whereas the 12 cases of 30 cases were moderately sensitive to bortezomib.…”
Section: Intracellular Anti‐apoptotic Proteins As Targeted Therapymentioning
confidence: 99%
“…182 Bortezomib also improves the response of myelomonocytic leukemic cells to tumor necrosis factor–related apoptosis-inducing ligand (TRAIL) in vitro, which is also related to bortezomib-mediated abrogation of NF-κβ activation, downregulation of the anti-apoptotic proteins C-FLIP and XIAP and expression of the TRAIL receptors DR4 and DR5. 183,184 …”
Section: Proteasome Inhibitorsmentioning
confidence: 99%
“…181183 Cytokine release syndrome was observed, manifested with fever, rigors, and hypoxia, which could be ameliorated by steroid prophylaxis. 184 Approximately 15% of patients experienced CNS complications, including convulsions and encephalopathy, which were reversible after drug withdrawal. 362364 Wong and colleagues demonstrated recently the activation of T cell cytotoxicity against B-precursor CLL (B-CLL) following exposure to Blinatumomab in vitro.…”
Section: Immunotherapy: Monoclonal and Bispecific Antibodiesmentioning
confidence: 99%